Kepemimpinan, Tata Kelola, dan Lingkungan Organisasi sebagai Penentu Motivasi dan Kinerja Pegawai pada Lembaga Sektor Publik - Indira Yuana; Mahmudin A. Sabilalo; Fauzih Fauzih; Ade Imam Muttaqien Halim (Society, 2025)
This study examines the influence of leadership style, organizational environment, and good governance on employee motivation and performance at the Southeast Sulawesi Provincial Plantation and Horticulture Office. Using a quantitative approach and Partial Least Squares (PLS) analysis, data were collected from employees within the same institution. The results reveal that leadership, governance, and a conducive organizational environment significantly enhance employee motivation. However, the direct impact of the organizational environment on performance appears limited, suggesting that employees may not prioritize environmental factors when evaluating their performance. The study highlights that effective leadership and strong governance structures play a crucial role in fostering motivation, leading to improved performance. These findings emphasize integrating governance and leadership strategies to support sustainable institutional success.